Các hợp chất phenolic phân lập từ lá cây nhội Bischofia javanica (Blume) - Mai, Nguyễn Thị (Vietnam Journal of Chemistry, 2017)
Six phenolic compounds including vitexin 2-O-β-D-glucopyranoside (1), vitexin (2), quercetin 3-rutinoside (3), quercetin (4), caffeoylglycolic acid methyl ester (5), and caffeic acid methyl ester (6) were isolated from the methanol extract of Bischofia javanica. Their chemical structures were characterized by nuclear magnetic resonance spectra, and as well as in comparison with those reported in the literature. Keywords. Bischofia javanica, phenolic, kaempferol, quercetin